Hanaw: A story of forgetting and remembrance - Nunez, Ana Margarita R. (Animo Repository, 2024)
This project explores and enlarges upon the idea of fiction as a form of siege through a novel that chronicles the experiences of an Iliganon family. The narrative design of the novel consists of three threads of story, one that takes place in the contemporary era, one during the Second World War, and one during the 1750s, at the time of the Moro Wars. The 18th century narrative serves as a staging point, while the wartime and contemporary narratives converge to foreground the idea of simultaneity and the importance of liberating the ideas of time and history from hegemonic constructions. The contemporary storyline is narrated in the first person and provides a frame or anchor for the stories of the past. The stories engage with issues of colonization and representation, and with ideas of power and desire vis-a-vis culture and history. The dynamics of the siege are illustrated via the encounter between opposing elements of old and new, tradition and improvisation, oral and written narrative and so forth which result in eventual collapse and reintegration. This is also an attempt to write an “Iliganon” novel that, while being ostensibly a work of fiction, utilizes the idea of “hanaw” as a means of describing and preserving local histories and oral accounts, certain manners of speaking, beliefs, accounts of physical spaces or events of significance before they are lost through the homogenizing forces of global capitalism. Keywords: fiction, siege, time, Iligan, history, novel